2023
DOI: 10.1007/s10991-023-09321-1
|View full text |Cite
|
Sign up to set email alerts
|

How do Law Students Develop Commercial Awareness? Listening to the Student Voice on the Roles of the Law School and the Law Student in Developing Commercial Awareness

Abstract: This article provides an authentic, student-centred account of how law students develop their commercial awareness on their journey to graduate employment. Drawing on data collected from a two year research study involving law students going through the graduate interview process, this article presents the first detailed empirical findings on how, when and why law students develop their commercial awareness. This data is important because law students have a wide range of available career options and commercia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…In a study of law students' attitudes towards commercial awareness, McConnell found that many students did not start to deliberately develop their commercial awareness until later in their degrees; this may negatively affect their chances of securing employment at top firms, which often target second-year students. 17 With such importance placed on employability and developing the relevant skills, getting involved with employability-related information skills training could be a valuable way for librarians to build relationships with academics and students and to raise the profile of the library within their institutions.…”
Section: Librarians Commercial Awareness and Employabilitymentioning
confidence: 99%
“…In a study of law students' attitudes towards commercial awareness, McConnell found that many students did not start to deliberately develop their commercial awareness until later in their degrees; this may negatively affect their chances of securing employment at top firms, which often target second-year students. 17 With such importance placed on employability and developing the relevant skills, getting involved with employability-related information skills training could be a valuable way for librarians to build relationships with academics and students and to raise the profile of the library within their institutions.…”
Section: Librarians Commercial Awareness and Employabilitymentioning
confidence: 99%